If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + 2) + -7 = 2(y + -7) Reorder the terms: 6(2 + y) + -7 = 2(y + -7) (2 * 6 + y * 6) + -7 = 2(y + -7) (12 + 6y) + -7 = 2(y + -7) Reorder the terms: 12 + -7 + 6y = 2(y + -7) Combine like terms: 12 + -7 = 5 5 + 6y = 2(y + -7) Reorder the terms: 5 + 6y = 2(-7 + y) 5 + 6y = (-7 * 2 + y * 2) 5 + 6y = (-14 + 2y) Solving 5 + 6y = -14 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 5 + 6y + -2y = -14 + 2y + -2y Combine like terms: 6y + -2y = 4y 5 + 4y = -14 + 2y + -2y Combine like terms: 2y + -2y = 0 5 + 4y = -14 + 0 5 + 4y = -14 Add '-5' to each side of the equation. 5 + -5 + 4y = -14 + -5 Combine like terms: 5 + -5 = 0 0 + 4y = -14 + -5 4y = -14 + -5 Combine like terms: -14 + -5 = -19 4y = -19 Divide each side by '4'. y = -4.75 Simplifying y = -4.75
| (14+2x)(22+2x)=0 | | 3(x+8)=5(x+3)-x | | 1/2(x+4)=5 | | 3(x+8)=5(x+3) | | 308+72x+4x^2=0 | | n-3/8n=13 | | 4.34/567.8 | | 2=x/10 | | -3y+8=2(2y-3) | | X^2+11x+9=9 | | 2.52/0.4 | | -(3/5)x=(6/35) | | 28+x+90=180 | | (2x-3)(x-1)=6+2(x+2)(x+3) | | 3/21,1/15 | | x(5)=23 | | 9y-24=-3(-3y+8) | | 5x+3x=48 | | 18.4/2.3 | | 7(x-1)-3(2x+1)=0 | | 329.5/28.4 | | x^2+8x-128=0 | | 329.44/28.4 | | 7+3c-5-6c= | | 72/127+2/3 | | (10)x=6 | | 2x^2+7x-x^2+4=1 | | 6x^2+72x=-192 | | 7-6-2c+9c= | | 2r+6t= | | 5(7+p)=30 | | -7(3x+6)=-84 |